Pengaruh Kualitas Pelayanan Dan Fasilitas Terhadap Kepuasan Tamu Di Hotel Mercure Bali Legian - Dewangga, I Putu Gede Greza; Saharjo, Sulistyoadi Joko; Putra, Putu Guntur Pramana (Universitas Triatma Mulya, 2024)
With the existence of competition between hotels, management must be able to compete to provide satisfaction for guests to come to stay at the hotel they manage. One of the factors that influence guest satisfaction is the quality of service and facilities. This study aims to analyze the influence of service quality and facilities partially and simultaneously and to determine the influence of service quality and facilities on guest satisfaction at the Mercure Bali Legian Hotel. The sample collection method used was purposive sampling. The population in this study were guests staying at the Mercure Bali Legian Hotel, while the sample used in this study was 70 respondents. Data collection techniques by means of observation, distribution of questionnaires and documentation, and data analysis techniques using multiple linear regression. The results of this study show that partially service quality has a positive and significant effect on guest satisfaction at the Mercure Bali Legian Hotel. Partially, facilities have a positive and significant effect on guest satisfaction at the Mercure Bali Legian Hotel. Simultaneously the quality of services and facilities has a positive and significant effect on guest satisfaction at the Mercure Bali Legian Hotel. The influence of service quality and facilities on guest satisfaction at the Mercure Bali Legian Hotel is 34.6%, while the remaining 65.4% is influenced by other variables not included in this study.